The effects of flipped learning in enhancing student's learning experience and learning satisfaction in the ESL reading classroom - Hassanuzin, Salsabilla; Soo, Kum Yoke (Centre of Foundation Studies, International Islamic University Malaysia, 2023)
The integration of blended learning has proven that learning can be more impactful and meaningful for the English as Second Language (ESL) classroom. Yet, with limited classroom time and passive learning environments, they have been found to hinder learning processes which can be solved through flipped learning. Flipped learning was popularized by Bergman and Sams and practised at Khan Academy before 2010. The traditional lesson is delivered outside the classroom in the flipped classroom, while the homework or assignments are done inside the classroom. Research on the implementation of flipped learning with ESL reading classrooms to gauge learning experience and satisfaction is scarce. Therefore, this study applied a quantitative approach in describing the flipped learning treatment on ESL learners in an ESL reading classroom. To find out the effects of flipped learning treatment on students’ learning experience, a survey named Student Assessment Survey (SAS) was administered. The survey explored the students’ experience and their learning satisfaction in a flipped learning environment. The SAS data showed that students preferred flipped classrooms. They experienced an improved understanding of English and learned to analyse texts better. It was also found that the educator played a vital role in facilitating understanding of the lesson via flipped learning. Therefore, flipped learning is very useful for educators to implement a quality learning environment in the classroom.